PECULIARITIES OF CURRENCY AND LEGAL STATUS OF INTERNATIONAL COMPANIES IN THE RUSSIAN FEDERATION - T. Gadzhiev (Гуманитарные и юридические исследования)
This article considers the speciics of the legal situation of international companies as participants in currency and legal relations. The urgency of this problem is due, on the one hand, to the need for sustainable development of the domestic economy, and, on the other hand, to ensure its security, in conditions of increasing sanctions pressure from a number of Western countries. At present, the priority of the economic policy of Russia is the deoffshorization of the economy. One of the important steps in the implementation of this policy was the creation of special administrative districts which are intended to become a kind of domestic offshore with a preferential legal regime. The legislator, in order to stimulate the return of domestic capital from offshore jurisdictions, established a preferential regime of currency regulation and control for international companies, created on the territory of special administrative districts. The article considers the theoretical basis for deining the concept of currency and legal status, analyses changes in currency legislation that identify international companies as currency non-residents, justiies the idea of preferential nature of currency regulation and control of activities of international companies, considers risks of classiication of international companies as non-residents. It is also justified that the establishment of a regime of no currency restrictions in the territories of special administrative regions will increase the investment attractiveness of these territories and will correspond to the global trend of liberalization of currency regulation. The author points to the fact that the changes considered in the currency legislation are intended to create the most favourable regime of currency regulation, which encourages the re-registration of foreign organizations as international companies.